THE EFFECT OF FINANCIAL RATIOS ON FINANCIAL PERFORMANCE AMONG BANKING COMPANIES - Cathleen, Annetta; Ekadjaja, Agustin (Graduate Program of Universitas Tarumanagara, 2023)
This study was conducted to obtain empirical evidence related to the effect of loan to deposit ratio, capital adequacy ratio, debt to equity ratio, and operational efficiency ratio on the financial performance of banking companies listed on the Indonesia Stock Exchange for a three-year period, which is 2017-2019. The research design used is descriptive research in describing the relationship between the independent variables and the dependent variable. The research method used is purposive sampling, with amounted to 29 companies that meet the criteria. Furthermore, this study used EViews 12 Student Version Lite application in the data processing. The results of this study indicate that the operational efficiency ratio influences the financial performance of banking companies. Meanwhile, loan to deposit ratio, capital adequacy ratio, and debt to equity ratio does not affect banking companies' financial performance.